2011
DOI: 10.5586/asbp.2003.043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of cowslip (Primula veris L.) populations (West Poland)

Abstract: Genetic variation of twelve Polish populations of Primula veris L. from western Poland was investigated in respect of six enzyme systems: 6-phosphogluconate dehydrogenase (6PGD), diaphorase (DIA), menadione reductase (MNR), formate dehydrogenase (FDH), isocitrate dehydrogenase (IDH) and glutamate oxaloacetate transaminase (GOT). Only two of them (6PGD and DIA) were polymorphic and all populations were compared according to four loci and eight alleles. For 6PGD only one out of the two detected loci (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Although Morozowska (2002) found that the majority of seeds obtained from natural populations in Poland appeared to be viable by a tetrazolium test (mean 88%, range 83-92%), seed germination rates were surprisingly variable. Poor germination rates are usually due to dormancy (Thompson et al 1997).…”
Section: Floral and Seed Charactersmentioning
confidence: 97%
See 2 more Smart Citations
“…Although Morozowska (2002) found that the majority of seeds obtained from natural populations in Poland appeared to be viable by a tetrazolium test (mean 88%, range 83-92%), seed germination rates were surprisingly variable. Poor germination rates are usually due to dormancy (Thompson et al 1997).…”
Section: Floral and Seed Charactersmentioning
confidence: 97%
“…(2004), who showed increasing levels of (biparental) inbreeding at high plant densities, which they, at least partly, attributed to pollinator behaviour combined with restricted seed dispersal. On the other hand, Antrobus & Lack (1993) and Morozowska & Krzakowa (2003) argued that long‐distance pollen dispersal across populations is one of the most plausible explanations for the low genetic differentiation ( F ST < 0.102) that they observed among P. veris populations in the Oxford region and western Poland, respectively. Because P. veris flowers at the time that queen Bombus spp., Anthophora spp.…”
Section: Floral and Seed Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…The current supply of saponins (in the international trade market) extracted from plants grown conventionally in the field is generally considered a laborious and low yielding process. This, together with cultivation-focused problems of P. veris crops [13,44], has resulted in the exploitation of different biotechnological systems for root biomass production similar to other plant species such as Datura stramonium and Hyoscyamus muticus [45], Atropa belladonna [45,46], and Panax ginseng [21], among others. In addition, the collection of cowslip raw materials from natural resources does not guarantee high quality, as concentrations of the biologically active compounds, similarly to many other medicinal plants, very often may vary [47].…”
Section: Discussionmentioning
confidence: 99%
“…The valuable secondary metabolites (SMs) produced in the underground organs of P. veris can be obtained only from cultivated plants [11]. In the majority of Primula species, including P. veris, there are well-known difficulties with seed germination under greenhouse or field conditions [11,12], therefore, alternative ways such as in vitro culture have been suggested for producing plant raw material for the pharmaceutical industry from the protected plant species in a relatively short time [13].…”
Section: Introductionmentioning
confidence: 99%